Integrated analysis reveals distinct molecular, clinical, and immunological features of B7‐H3 in acute myeloid leukemia. (25th September 2021) - Zhang, Ling‐yi; Jin, Ye; Xia, Pei‐hui; Lin, Jiang; Ma, Ji‐chun; Li, Ting; Liu, Zi‐qi; Xiang, He‐lin; Cheng, Chen; Xu, Zi‐jun; Zhou, Hong; Qian, Jun
Abstract: The role of B7 ‐ H3 in acute myeloid leukemia (AML) is not fully understood. Two previous studies investigating its expression and significances in AML are partially different. In this study, we aimed to systematically characterize the genomic and immune landscape in AML patients with altered B7 ‐ H3 expression using multi‐omics data in the public domain. We found significantly increased B7 ‐ H3 expression in AML compared to either other hematological malignancies or healthy controls. Clinically, high B7 ‐ H3 expression was associated with old age, TP53  mutations, wild‐type WT1 and CEBPA, and the M3 and M5 FAB subtypes. Moreover, we observed that increased B7 ‐ H3 expression correlated significantly with a poor outcome of AML patients in four independent datasets. Gene set enrichment analysis (GSEA) revealed the enrichment of the "EMT" oncogenic gene signatures in high B7 ‐ H3 expressers. Further investigation suggested that B7 ‐ H3 was more likely to be associated with immune‐suppressive cells (macrophages, neutrophils, dendritic cells, and Th17 cells). B7 ‐ H3 was also positively associated with a number of checkpoint genes, such as VISTA ( B7 ‐ H5 ), CD80 ( B7 ‐ 1 ), CD86 ( B7 ‐ 2 ), and CD70 . In summary, we uncovered distinct genomic and immunologic features associated with B7 ‐ H3 expression in AML. This may lead to a better understanding of the molecular mechanisms underlying B7 ‐ H3 dysregulation in AML and to the development of novel therapeutic strategies. Abstract : In this paper, we found significantly increased B7‐H3 expression in AML compared to either other hematological malignancies or healthy controls. Importantly, we observed that increased B7‐H3 expression correlated significantly with a poor outcome of AML patients in four independent datasets. We also uncovered distinct genomic and immunologic features associated with B7‐H3 expression in AML.